Unknowability at the Heart of Science and Mathematics. - Wolchover, Natalie (Social Research)
The article focuses on concept of unknowability in science has been compared to a painting from 1927 by the German artist Paul Klee. It mentions quantum mechanics shows that the universe is largely unknowable in a certain sense and uncertainty and probabilistic nature of our quantum mechanical universe present a fundamental barrier to knowability. It also mentions mathematician David Hilbert argued that all mathematical truths could be ascertained by human reasoning. It discusses mathematician Gregory Chaitin defines the probability that a random computer program will halt, completing a calculation and providing an answer instead of getting stuck in an infinite loop.